PREVENTING INTERNAL SHORT CIRCUIT IN A LITHIUM-ION BATTERY CELL - VICHARE NIKHIL MANOHAR; RICHMOND MARC ALLAN; THOMPSON RICHARD C; MILLER BRUCE A; MARTINEZ MAUREEN EMILY (2015)
Embodiments of methods for preventing internal short circuits in a lithium-ion battery cell. In an embodiment, a method of manufacturing a lithium-ion battery cell may include providing a cathode, providing an anode, providing a separator disposed between the cathode and the anode, and covering an edge of the cathode to prevent a short between the cathode and the anode through the separator. The method may also include winding the cathode, the anode, and the separator into an electrode roll.